Psychology of trauma 101 - Ruglass, Lesia M.; Kendall-Tackett, Kathleen A. (Psych 101 series., 2014)
Mental health professionals who don't specialize in trauma practice are discovering more and more frequently that trauma survivors represent a high percentage of their client population. Trauma 101 is a concise, current, balanced, and accessible overview of one of the most pervasive, yet controversial psychological issues faced today. It is grounded in the most up-to-date research and theories on trauma and its effects, and covers not only the concepts of what trauma is and the ways in which different kinds of traumas affects people, but also considers how it is diagnosed in the wake of the DSM-5 and is treated with both conventional and alternative methods.